Mike Barrowman's full stroke at 120 m of his 200 m breaststroke gold medal race at the Barcelona Olympic Games 1992 - Rushall, B. S. (1999)
Video pictures (14 frames) and the appropriate technical/ biomechanical explanations for Mike Barrowman's Full Stroke at 120 m of His 200 m Breaststroke Gold Medal Race at the Barcelona Olympic Games 1992.